Efficacy of an interdental brush in cleaning artificial plaque on a 3D-printed model base - Seo Eun Kim; Eun Sun Song; Seung Pyo Lee (BMC, 2022)
Abstract Background Among interdental cleaning aids (ICAs), interdental brushes (IDBs) are in the spotlight because they can effectively remove plaque from interdental surfaces. Guidance on the correct use of ICAs, such as IDBs, is required to prevent dental plaque accumulation. Since it is impossible to confirm the interdental proximal surface unless extracted, it is difficult to conduct quantitative experiments. This study presented an efficient way to evaluate IDBs by realizing dental structures and embrasures using a Dental computer-aided design (CAD) software and a 3D printer. Methods Two different sizes of embrasure (0.7 and 1.2 mm) crown models were prepared with CAD software and a 3D printer. To evaluate the cleaning efficacy of IDBs of each size (0.6, 0.7, 0.8, 1.0, 1.2, and 1.5 mm diameters), the 9th cycle of brush move was performed where artificial plaque was spread and a digital camera was used to record the process. The pixels and percentage of cleaning from the recorded digital images were analyzed. Results The plateau was formed after the 5th brushing cycle under all conditions-after the 5th cycle, the cleaning efficacy of the two crown models was 69.3-86.4% and 49.8-75.4%. In these results, the optimal diameters for the IDB were 1.2 and 1.5 mm for embrasure sizes of 0.7 and 1.2 mm, respectively. Moreover, the cleaning efficacy was the highest at 86.4% and 75.4% after the 9th cycle. Conclusions The 3D-printed model base for the human oral embrasure structure is an adequate model to test artificial plaque removal using IDB. The use of IDBs for more than five cycles does not support the conventional idea that a greater number of IDB brushing moves is more effective in a statistically substantial manner.